Proceedings of the 17th ACM Conference on Interaction Design and Children 2018
DOI: 10.1145/3202185.3210779
|View full text |Cite
|
Sign up to set email alerts
|

Investigating query formulation assistance for children

Abstract: Popular tools used to search for online resources are tuned to satisfy a broad category of users-primarily adults. Because children have specific needs, these tools may not always be successful in offering the right level of support in their quest for information. While search tools often provide query assistance, children still face many difficulties expressing their information needs in the form of a query. In this paper, we share results from our ongoing research work focused on understanding children's int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…We obtained query and query interaction logs from a previous workin-progress study that reported on survey data and processes [16] from a pilot study. The pilot study was conducted over two 40-minute search sessions with 8 children (5 girls, and 3 boys) ages 6-10.…”
Section: Query Suggestion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained query and query interaction logs from a previous workin-progress study that reported on survey data and processes [16] from a pilot study. The pilot study was conducted over two 40-minute search sessions with 8 children (5 girls, and 3 boys) ages 6-10.…”
Section: Query Suggestion Methodsmentioning
confidence: 99%
“…To our knowledge, there is no de-facto query formulation strategy favored by children. To better understand how existing strategies address children's query formulation problems and the varying ways to help children formulate queries when using search tools, we build upon the results presented by the authors in [16] and ask these research questions:…”
Section: Introductionmentioning
confidence: 99%
“…Anuyah et al [46] compared general purpose interface elements in IR systems with child-specific elements, focusing on query suggestions for children [47,48]. Only three of the eight children in Anuyah et al's [46] study seemed to have noticed the different query suggestions. It was not clear from the study report if children were using query suggestions unprompted.…”
Section: Children's Use Of Information Retrieval Systemsmentioning
confidence: 99%
“…Given that providing suitable spelling suggestions in an interactive spellchecker is truly a ranking problem rather than a classification problem, as well as the behavior shown in children to have a propensity to interact with higher ranked alternatives [33,2], we also use the learning-to-rank (LTR) model LambdaMART [8]. While, the use of LTR models has not knowingly been explored for spellchecking, they have proven effective at similar ranking problems such as large scale search, query suggestions, and recommendation [52].…”
Section: Age Of Acquisition (Aoamentioning
confidence: 99%
“…A higher MRR value indicates a higher average ranking for the gold standard. Given children's propensity to click on higher ranked alternatives for spelling suggestions [15] as well as other areas of search [2,33], it is crucial to rank the gold standard highly. Taken together, these two metrics measure how well each spellchecker is at finding the intended word (Hit Rate) and how well it is ranked (MRR).…”
Section: Metricsmentioning
confidence: 99%